SHORT STORY AS A GENERIC AND DISCURSIVE PHENOMENON IN THE SHORT STORY COLLECTION TAMING THE BITCH BY VENKO ANDONOVSKI (Journal of Contemporary Philology, 2020)
This text represents an attempt of close-reading and interpretation of the work by the Macedonian writer and university professor Venko Andonovski and his short stories in the book titled Taming of the Bitch. The book represents a revalorization of author’s creative models, as well as re-actualization of inherited generic, stylistic, motif literary elements, overall. The analysis investigates the classic concept of short story as a genre, which can be seen through the examination of its generic properties, and these theses are later re-evaluated according to short story’s potential as a discursive phenomenon. We interpreted the stories following the same order of their appearance in the book, since this sequence refers to the subsequent change of author’s point of view regarding short story (novel) as a genre. It is expected that several questions will remain open, especially the ones concerning the validity of generic expectations, or the notion of generic structure. These short stories affirm the active confrontation of various voices of the epoch, i.e., the literary mass-production that provides instant variants of lots of misunderstood aspects, concerning the phenomenon called proficiency in literary text creation.
Keywords: short story; genre; Macedonian literature; discourse; mass culture